Utilization of Anabolic Implants and Individual Supplementation on Muscle Growth and Protein Turnover During Backgrounding of Beef Steers - J. Luke Jacobs; Elizabeth Leonard; Nishanth Tharayil; Susan K. Duckett (Animals)
Weaned Angus-cross steers (n = 69; body weight [BW] = 233 ± 29 kg) were used for the following purposes: (1) develop an assay to measure 3-methylhistidine (3MH) in blood samples to monitor changes in protein turnover, and (2) evaluate the effects of an implant (Revalor-G, 40 mg of trenbolone acetate, 8 mg of estradiol) or an implant plus individual supplementation via SuperSmart Feeder (SSF; C-Lock Inc., Rapid City, SD, USA) on animal growth, muscle growth, and nitrogen retention patterns in backgrounded beef steers. Steers were blocked by weight, trained to precision supplementation via SSF, and then assigned to one of three treatments: (1) grazing only [G], (2) grazing with implant [GI], or (3) grazing with implant plus individual animal supplementation via SSF at 0.75% BW [GIS] for 56 d of grazing study. Steers grazed a cowpea and pearl millet mixture until d 42, when forage became limiting, and steers were transitioned to an oat and annual ryegrass baleage. Steers were weighed and blood was collected every 14 d to determine plasma urea nitrogen (PUN), creatinine (CREAT), and 3-methylhistidine (3MH) concentrations. Ultrasound measurements of ribeye area (REA) were collected on d 0, 28, and 56. Data were analyzed using the GLIMMIX with treatment, day, and two-way interaction in the model. A novel, robust method for the determination of 3MH was developed and validated. The development of this 3MH method allows us to monitor changes in protein turnover in cattle over time, a metric which is related to production efficiency. A treatment-by-day interaction (p = 0.0050) was observed for BW and REA. Steer BW did not differ (p > 0.05) on d 0, 14, or 28 between treatments; however, on d 42, GI and GIS steers had a greater (p < 0.01) BW than G steers. On d 56, BW was greater (p < 0.0001) for GIS than GI and G, which not differ (p > 0.05). Total BW gain during the 56 d study was greater (p < 0.001) by 54% for GIS compared to GI or G. For GI, the total BW gain was greater (p < 0.01) by 18% compared to G. On d 56, the REA of GI and GIS steers was greater (p < 0.001) than of G steers. Steers in the GI treatment group had a greater PUN and PUN–CREAT ratio concentrations than the GIS steers. Both G and GI steers had greater 3-methylhistidine (3MH) concentrations compared to GIS steers on d 28. Our results demonstrate that the supplementation of implanted steers improves growth and improves nitrogen utilization during backgrounding on forage diets. This research illustrates that animal and muscle growth may be limited in grazing animals implanted with combination implants (estrogenic and androgenic compounds) when supplementation is not included.